Jubal [videorecording (DVD)] - Jones, Kent, 1964- (Criterion collection, 2013)
In this Shakespearean tale of jealousy and betrayal, a man who is an honorable itinerant cattleman, befriended and hired by a bighearted ranch owner despite his unwillingness to talk about his past. When the new hand becomes the target of the flirtatious attentions of the owner's bored wife and is entrusted by the boss with a foreman's responsibilities, his presence at the ranch starts to rankle his shifty fellow cowhand.